Electronic properties of CoSi2 film in ion bombing by oxygen ions - Donaev S.B., Umirzakov B.E., Abduvayitov A.A, (International Journal of Advanced Science and Technology, 2020)
The morphology, composition, and electronic properties of the CoSiO film obtained on theCoSi2/Si(111) surface by implantation of O2+ ions in combination with annealing were studied. Theparameters of energy bands are determined and information on the density of state of electrons of thevalence band and conduction band is obtained. In particular, it was shown that the band gap of thisfilm is ~ 2.4 eV.